A porous C / Mn x Fe 1-x O / Mn y Fe 3-y O 4 Composite wave absorbing material and preparation method thereof
By preparing porous C/MnxFe1-xO/MnyFe3-yO4 composite wave absorbing material, it is heated and burned by a uniform mixed solution based on manganese salt and iron salt, combined with annealing treatment and phenolic polycondensation reaction, and finally carbonized in a hot atmosphere, achieving organic composite of C, MnxFe1-xO and MnyFe3-yO4, solving the problem of single composite method and fewer composite types in the prior art, and achieving excellent microwave absorption performance of the material.
Patent Information
- Application Number
- CN202411762252.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-03
AI Technical Summary
In the prior art, the composite method is single and there are fewer types of composites, making it difficult to further improve the wave absorbing performance of the material.
By preparing porous C/MnxFe1-xO/MnyFe3-yO4 composite wave absorbing material, it is heated and burned by a uniform mixed solution based on manganese salt and iron salt, combined with annealing treatment and phenolic polycondensation reaction, and finally carbonized in a hot atmosphere, achieving organic composite of C, MnxFe1-xO and MnyFe3-yO4.
The two elements of manganese and ferromanganese are mutually soluble and adjustable in the oxide and ferrite lattice, and the electromagnetic wave absorption performance is optimized, and the material shows excellent microwave absorption performance.
Smart Images

Figure CN119231190B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electromagnetic materials, and specifically relates to a porous C / Mn x Fe 1-x O / Mn y Fe 3-y O4 composite absorbing material and preparation method thereof. Background Art
[0002] The composite of carbon materials and magnetic materials, including metal alloys and oxides containing iron, cobalt, nickel, neodymium, boron, samarium, etc., is a hot material in the field of electromagnetic stealth research in recent years. This is mainly because the composite of dielectric materials and magnetic materials helps to achieve impedance matching of electromagnetic waves, so that electromagnetic waves can enter the interior of the material and attenuate electromagnetic waves. In addition, the magnetic / dielectric composite can achieve the effect of dielectric loss and magnetic loss synergistically attenuating electromagnetic waves, thereby improving the wave absorption performance. From the preparation point of view, carbon materials can be prepared in a variety of ways, and the raw materials for preparation are cheap and abundant. In addition, the dielectric properties will be significantly different if the degree of graphitization is different, and it has excellent controllability. Magnetic metals, alloys and their oxides are also cheap and easy to prepare. Therefore, the composite of the two has a natural advantage.
[0003] At present, the research on this kind of materials still has the problem of single composite method and few composite types, which makes it difficult to further improve the material's wave absorption performance. Therefore, the preparation of carbon-based magnetic / dielectric multi-composite materials is of great significance to promote the improvement of the material performance of this system. x Fe 1-x O and Mn y Fe 3-y There is no report on the porous absorbing material composed of three organic compounds of O4. Summary of the invention
[0004] The object of the present invention is to provide a porous C / Mn x Fe 1-x O / Mn y Fe 3-y O4 composite absorbing material and preparation method thereof, so as to realize the adjustable mutual dissolution of two elements of manganese and iron in oxide and ferrite lattices, and optimize its electromagnetic wave absorption performance.
[0005] To achieve the above object, the technical solution adopted by the present invention is as follows: As a first aspect, the present invention provides a porous C / Mn x Fe 1-x O / Mn y Fe 3-yThe preparation method of O4 composite wave absorbing material comprises the following steps: taking manganese salt and iron salt as the basis, adding one of citric acid, amino acid, tartaric acid, gluconic acid, polyvinyl pyrrolidone and sugar, dissolving in an aqueous solution, and uniformly stirring by ultrasonication to obtain a homogeneous mixed solution; heating the homogeneous mixed solution until a combustion reaction occurs to obtain a porous substance, and annealing the obtained porous substance; dissolving the annealed substance in water and ethanol, adding phenol monomers and aldehyde monomers to carry out a condensation reaction, centrifugally separating, washing with water and ethanol for multiple times, and vacuum drying to obtain a precursor; carbonizing the precursor in a hot atmosphere to obtain a porous C / Mn x Fe 1-x O / Mn y Fe 3-y O4 composite absorbing material, wherein 0<x<1, 0<y<3.
[0006] Furthermore, in the homogeneous mixed solution, the molar ratio of manganese ions to iron ions is 0.01-100, and the total concentration of metal ions is 0.05-10 mol / L.
[0007] Furthermore, in the homogeneous mixed solution, the molar ratio of the concentration of one of citric acid, amino acid, tartaric acid, gluconic acid, polyvinyl pyrrolidone, and sugar to the total concentration of metal ions is 0.1-10.
[0008] Furthermore, the homogeneous mixed solution is heated until a combustion reaction occurs, specifically: the heating temperature is set at 200-500° C., and finally a combustion reaction occurs to obtain a porous substance.
[0009] Furthermore, the annealing treatment is specifically as follows: placing the obtained porous material in a muffle furnace and keeping it at 300-1000° C. for 1-10 h, with the heating rate maintained at 1-10° C. / min.
[0010] Furthermore, the annealed substance is dissolved in water and ethanol, and a phenolic monomer and an aldehyde monomer are added to carry out a polycondensation reaction, specifically: the annealed substance is dissolved in a mixed solution of water and ethanol, the volume ratio of water to ethanol is maintained at 5:2, the concentration of the annealed substance in the mixed solution of water and ethanol is 0.1-10 g / L, ultrasonic stirring is performed until it is evenly dispersed to obtain a mixed suspension, a phenolic monomer and ammonia water are added and stirring is continued until it is evenly dissolved, the mass ratio of the annealed substance to the phenolic monomer is 1:0.1-1:10, and the volume ratio of ammonia water to the mixed solution of water and ethanol is 1:50-1:500; then an aldehyde monomer is added and stirred for reaction for 5-72 h, the molar ratio of the phenolic monomer to the aldehyde monomer is 1:1-1:3, and after the reaction is completed, centrifugation is performed to separate the powdered substance, which is washed at least three times with a mixed solution of water and ethanol, and dried in a vacuum drying oven overnight to obtain a precursor.
[0011] Furthermore, the phenolic monomer is resorcinol or hydroquinone.
[0012] Furthermore, the aldehyde monomer is formaldehyde or acetaldehyde.
[0013] Furthermore, the hot atmosphere carbonization is specifically as follows: placing the precursor in a tube furnace, keeping the temperature at 300-1000°C for 1-72 h under an inert atmosphere, and maintaining the heating rate at 1-10°C / min.
[0014] As a second aspect, the present invention provides a porous C / Mn x Fe 1-x O / Mn y Fe 3-y The O4 composite wave absorbing material is prepared by adopting the preparation method.
[0015] Compared with the prior art, the present invention has the following beneficial effects: the present invention realizes the x Fe 1-x O and Mn y Fe 3- y The composite of three substances, O4, achieves the purpose of mutual solubility of two elements, manganese and iron, in the two lattices of metal oxide and ferrite, and the porous C / Mn x Fe 1-x O / Mn y Fe 3-y O4 composite materials have excellent wave absorption properties and have application potential in the electromagnetic field. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The porous C / Mn prepared by the present invention x Fe 1-x O / Mn y Fe 3-y SEM photo of O4 composite absorbing material;
[0017] Figure 2 The porous C / Mn prepared by the present invention x Fe 1-x O / Mn y Fe 3-y TEM photo of O4 composite absorbing material;
[0018] Figure 3 The porous C / Mn prepared by the present invention x Fe 1-x O / Mn y Fe 3-y XRD pattern of O4 composite absorbing material;
[0019] Figure 4The porous C / Mn prepared by the present invention x Fe 1-x O / Mn y Fe 3-y Raman spectrum of O4 composite absorbing material;
[0020] Figure 5 The porous C / Mn prepared by the present invention x Fe 1-x O / Mn y Fe 3-y Hysteresis loop of O4 composite absorbing material;
[0021] Figure 6 The porous C / Mn prepared by the present invention x Fe 1-x O / Mn y Fe 3-y Reflection loss curve of O4 composite absorbing material. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It is worth noting that the following embodiments cannot be understood as limiting the scope of protection of the present invention, and those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above invention content, which still fall within the scope of protection of the present invention.
[0023] The terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0024] The present invention provides a porous C / Mn x Fe 1-x O / Mn y Fe 3-y The preparation method of O4 composite absorbing material comprises the following steps:
[0025] (1) Dissolve manganese salt, iron salt and citric acid (or amino acid, tartaric acid, gluconic acid, polyvinyl pyrrolidone, sugar) in an aqueous solution, wherein the molar ratio of manganese ion to iron ion is between 0.01 and 100, the total concentration of metal ions is maintained at 0.05 to 10 mol / L, the molar ratio of citric acid (or amino acid, tartaric acid, gluconic acid, polyvinyl pyrrolidone, sugar) to the total concentration of metal ions is maintained at between 0.1 and 10, and the mixed solution is ultrasonically stirred to be uniform;
[0026] (2) heating the homogeneous mixed solution at a temperature between 200°C and 500°C, and finally causing a combustion reaction to obtain a porous material;
[0027] (3) annealing the obtained porous material, specifically: placing it in a muffle furnace and keeping it at 300-1000 °C for 1-10 h, with the heating rate maintained between 1-10 °C / min;
[0028] (4) Dissolve the annealed material in a mixed solution of water and ethanol, keeping the volume ratio of water to ethanol at 5:2, and add phenolic monomer (resorcinol or hydroquinone) and ammonia water to the mixed suspension after ultrasonic stirring until it is evenly dispersed, and then add aldehyde monomer (formaldehyde or acetaldehyde) and stir to react for 5~72 hours. After the reaction is completed, centrifuge the mixed suspension to separate the powdered material, then wash it with a mixed solution of water and ethanol at least three times, and finally dry it in a vacuum drying oven overnight; wherein, the concentration of the annealed material in the mixed solution of water and ethanol is maintained at 0.1~10 g / L, the mass ratio of the annealed material to the phenolic monomer is 1:0.1~1:10, the molar ratio of the phenolic monomer to the aldehyde monomer is 1:1~1:3, and the volume ratio of ammonia solution (NH3, mass fraction 25.0~30.0%) and the mixed solution of water and ethanol is between 1:50~1:500;
[0029] (5) The material obtained in step 4 is placed in a tube furnace and kept at 300-1000 °C for 1-72 h under an inert atmosphere, with the heating rate maintained at 1-10 °C / min. Finally, C / Mn x Fe 1-x O / Mn y Fe 3-y O4 composite material.
[0030] The present invention prepares porous C / Mn by heating a uniform mixed solution containing manganese salt, iron salt and citric acid (or amino acid, tartaric acid, gluconic acid, polyvinyl pyrrolidone, sugar) to burn and oxidize, and then annealing to obtain manganese and iron oxides, forming polymers on the surface of the oxides through phenolic polycondensation reaction, and finally carbonizing by hot atmosphere. x Fe 1-x O / Mn y Fe 3-y O4 composite material. The present invention utilizes the preparation process to achieve C, Mn x Fe 1-x O and Mn y Fe 3-y O4 organic compound of three substances, such as Figure 1~Figure 2 The porous C / Mn x Fe 1-x O / Mn y Fe 3-ySEM and TEM photos of O4 composite absorbing materials, such as Figure 3 The XRD pattern is shown as Figure 4 The Raman spectrum shown in the figure shows the degree of carbonization. Figure 5 The hysteresis loop shown shows that it has soft magnetic properties, and Figure 6 As shown, its microwave absorption performance is good, and the strongest reflection loss is below -50 dB.
[0031] Example 1: A porous C / Mn x Fe 1-x O / Mn y Fe 3-y The preparation method of O4 composite absorbing material comprises the following steps:
[0032] (1) Dissolve 4.2 g manganese nitrate, 13.5 g ferric nitrate and 5 g aminoacetic acid in 500 mL deionized water and stir the mixed solution by ultrasonic stirring.
[0033] (2) The homogeneous mixed solution is heated at 270 °C, and a violent combustion reaction occurs to obtain a porous material;
[0034] (3) The obtained porous material was placed in a muffle furnace and kept at 700 °C for 2 h, with the heating rate maintained at 5 °C / min;
[0035] (4) Disperse 1 g of the substance obtained in step (3) in a mixed solution of 1000 mL of deionized water and 400 mL of anhydrous ethanol, stir ultrasonically until uniformly dispersed, add 1 g of resorcinol and 8 mL of ammonia water to the mixed suspension and continue stirring until uniformly dissolved, then add 8 mL of formaldehyde and stir to react for 24 h. After the reaction is completed, centrifuge the mixed suspension to separate the powdery substance, then wash it with a mixed solution of water and ethanol until the supernatant after centrifugation is colorless, and finally dry it in a vacuum drying oven overnight;
[0036] (5) The material obtained in step (4) was placed in a tube furnace and kept at 650 °C for 6 h under Ar atmosphere with a heating rate of 2 °C / min to obtain C / Mn x Fe 1-x O / Mn y Fe 3-y O4 composite material.
[0037] Example 2: A porous C / Mn x Fe 1-x O / Mn y Fe 3-y The preparation method of O4 composite absorbing material comprises the following steps:
[0038] (1) Dissolve 8.2 g manganese nitrate, 6.3 g ferric nitrate and 4 g citric acid in 300 mL deionized water and stir the mixed solution by ultrasonic stirring.
[0039] (2) The homogeneous mixed solution is heated at 300 °C, and a violent combustion reaction occurs to obtain a porous material;
[0040] (3) The obtained porous material was placed in a muffle furnace and kept at 650 °C for 3 h, with the heating rate maintained at 2 °C / min;
[0041] (4) Disperse 5 g of the substance obtained in step (3) in a mixed solution of 2000 mL of deionized water and 800 mL of anhydrous ethanol, stir ultrasonically until uniformly dispersed, add 2 g of hydroquinone and 15 mL of ammonia water to the mixed suspension and continue stirring until uniformly dissolved, then add 10 mL of acetaldehyde and stir to react for 24 h. After the reaction is completed, centrifuge the mixed suspension to separate the powdery substance, then wash it with a mixed solution of water and ethanol until the supernatant after centrifugation is colorless, and finally dry it in a vacuum drying oven overnight;
[0042] (5) The material obtained in step (4) was placed in a tube furnace and kept at 700 °C for 4 h under Ar atmosphere with a heating rate of 5 °C / min to obtain C / Mn x Fe 1-x O / Mn y Fe 3-y O4 composite material.
[0043] Example 3: The difference from Example 2 is that the type, amount and ratio of the metal element-containing substance added in step (1) can be changed; citric acid and aminoacetic acid can be changed to other substances, and the amount can also be changed; the volume of the aqueous solution can be changed; the temperature set in step (2) can be changed; the temperature, insulation time and heating rate set in step (3) can be changed; the amount, type and ratio of various reactants and solvents added in step (4) can be changed; the time of ultrasound and stirring can be changed; resorcinol or hydroquinone and formaldehyde or acetaldehyde can be changed to other types of polymerization monomers, and the initiation conditions of the reaction can also be adjusted; the type of inert atmosphere in step (5) can be changed, and the temperature, insulation time and heating rate can also be changed; the rest is the same as Examples 1 and 2.
[0044] In summary, the present invention provides a porous C / Mn x Fe 1-x O / Mn y Fe 3-y O4 composite absorbing material preparation method realizes C, Mn x Fe 1-xO、Mn y Fe 3-y The organic combination of O4 and manganese achieves the purpose of adjustable mutual solubility of the two elements of manganese and iron in the two lattices of metal oxide and ferrite, and the obtained composite material exhibits relatively excellent microwave absorption performance and has application potential in the electromagnetic field.
[0045] Those skilled in the art will readily appreciate other embodiments of the present application after considering the description and practicing the contents disclosed herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary technical means in the art that are not disclosed in the present application. The description and examples are intended to be exemplary only.
[0046] It should be understood that the present application is not limited to the structures that have been described above and shown in the accompanying drawings, and various modifications and changes may be made without departing from the scope thereof.
Claims
1. A porous C / Mn x Fe 1-x O / Mn y Fe 3-y The preparation method of O4 composite absorbing material is characterized in that: Based on manganese salt and iron salt, one of citric acid, amino acid, tartaric acid, gluconic acid, polyvinyl pyrrolidone and sugar is added, dissolved in aqueous solution, and ultrasonically stirred to obtain a homogeneous mixed solution; in the homogeneous mixed solution, the molar ratio of manganese ion to iron ion is 0.01-100, the total concentration of metal ions is 0.05-10 mol / L, and the molar ratio of the concentration of one of citric acid, amino acid, tartaric acid, gluconic acid, polyvinyl pyrrolidone and sugar to the total concentration of metal ions is 0.1-10; the homogeneous mixed solution is heated until a combustion reaction occurs to obtain a porous substance, and the obtained porous substance is annealed; the annealed substance is dissolved in water and ethanol, a phenolic monomer and an aldehyde monomer are added to carry out a condensation reaction, centrifugation, water and ethanol washing for multiple times, and vacuum drying to obtain a precursor; the precursor is carbonized in a hot atmosphere to obtain a porous C / Mn x Fe 1-x O / Mn y Fe 3-y O4 composite absorbing material, wherein 0<x<1, 0<y<3.
2. The porous C / Mn according to claim 1 x Fe 1-x O / Mn y Fe 3-y The preparation method of O4 composite absorbing material is characterized in that: The homogeneous mixed solution is heated until a combustion reaction occurs. Specifically, the heating temperature is set at 200-500°C, and finally a combustion reaction occurs to obtain a porous substance.
3. The porous C / Mn according to claim 1 x Fe 1-x O / Mn y Fe 3-y The preparation method of O4 composite absorbing material is characterized in that: The annealing treatment is specifically as follows: placing the obtained porous material in a muffle furnace and keeping it at 300-1000°C for 1-10 hours, with the heating rate maintained at 1-10°C / min.
4. The porous C / Mn according to claim 1 x Fe 1-x O / Mn y Fe 3-y The preparation method of O4 composite absorbing material is characterized in that: The method of dissolving the annealed substance in water and ethanol, and adding phenolic monomers and aldehyde monomers to carry out polycondensation reaction is specifically as follows: dissolving the annealed substance in a mixed solution of water and ethanol, maintaining a volume ratio of water to ethanol of 5:2, and a concentration of the annealed substance in the mixed solution of water and ethanol of 0.1-10 g / L, ultrasonically stirring until uniform dispersion to obtain a mixed suspension, adding phenolic monomers and ammonia water and continuing to stir until uniform dissolution, the mass ratio of the annealed substance to the phenolic monomer is 1:0.1-1:10, and the volume ratio of ammonia water to the mixed solution of water and ethanol is 1:50-1:500; then adding aldehyde monomers and stirring for reaction for 5-72 hours, the molar ratio of phenolic monomers to aldehyde monomers is 1:1-1:3, centrifuging after the reaction is completed, separating powdery substances, washing at least three times with a mixed solution of water and ethanol, and drying in a vacuum drying oven overnight to obtain a precursor.
5. The porous C / Mn according to claim 4 x Fe 1-x O / Mn y Fe 3-y The preparation method of O4 composite absorbing material is characterized in that: The phenolic monomer is resorcinol or hydroquinone.
6. The porous C / Mn according to claim 4 x Fe 1-x O / Mn y Fe 3-y The preparation method of O4 composite absorbing material is characterized in that: The aldehyde monomer is formaldehyde or acetaldehyde.
7. The porous C / Mn according to claim 1 x Fe 1-x O / Mn y Fe 3-y The preparation method of O4 composite absorbing material is characterized in that: The hot atmosphere carbonization is specifically as follows: placing the precursor in a tube furnace, keeping the temperature at 300-1000°C for 1-72 h under an inert atmosphere, and maintaining the heating rate at 1-10°C / min.
8. A porous C / Mn x Fe 1-x O / Mn y Fe 3-y O4 composite absorbing material, characterized in that: The preparation method is described in any one of claims 1 to 7.
Citation Information
Patent Citations
Method for preparing graphene / ferrite composite nanometer microspheres having high magnetic-electric performances
CN104941543A
Method for preparing nanometer MnFe2O4 / graphene composite material
CN104944474A